Cyclic-di-AMP Phosphodiesterase Elicits Protective Immune Responses Against Mycobacterium tuberculosis H37Ra Infection in Mice - Lu, Yanzhi; Ning, Huanhuan; Kang, Jian; Bai, Guangchun; Zhou, Lei; Kang, Yali; Wu, Zhengfeng; Tian, Maolin; Zhao, Junhao; Ma, Yueyun; Bai, Yinlan (Frontiers in Cellular and Infection Microbiology, 2022)
Lots of antigens from M. tuberculosis have been demonstrated as strong immunogens and proved to have application potential as vaccine candidate antigens. Cyclic di-AMP (c-di-AMP) as a bacterial second messenger regulates various bacterial processes as well as the host immune responses. Rv2837c, the c-di-AMP phosphodiesterase (CnpB), was found to be relative to virulence of M. tuberculosis and interference with host innate immune response. In this study, recombinant CnpB was administered by subcutaneous way to mice. We found that CnpB had strong immunogenicity and induced high levels of humoral response and lung mucosal immunity after M. tuberculosis intranasally infection. CnpB immunization stimulated the splenocytes proliferation and the increasing number of activated NK cells, but had little effects on Th1/Th2 cellular immune responses in spleens. However, CnpB induced significant Th1/Th2 cellular immune responses with a decreased number T and B cells in lungs, and significant recruits of CD4+ and CD8+ T cells after M. tuberculosis attenuated strain H37Ra infection. Besides, we first reported CnpB could stimulate IFN-β expression transitorily and inhibit autophagy of macrophages in vitro. In mice intranasally infection model, CnpB immunization alleviated pathological changes and reduced the M. tuberculosis H37Ra loads in lungs. Thus, our results suggested that the c-di-AMP phosphodiesterase CnpB interferes with host innate and adaptive immune responses and confers the protection against M. tuberculosis respiratory infection, which should be considered in vaccine development as well as drug target.